Atopic Dermatitis Studies through In Vitro Models - De Vuyst, Evelyne; Salmon, Michel; Evrard, Céline; Lambert de Rouvroit, Catherine; Poumay, Yves (Frontiers in Medicine, 2017)
Atopic dermatitis (AD) is a complex inflammatory skin condition that is not fully understood. Epidermal barrier defects and Th2 immune response dysregulations are thought to play crucial roles in the pathogenesis of the disease. A vicious circle takes place between these alterations and it can further be complicated by additional genetic and environmental factors. Studies investigating in depth the aetiology of the disease are thus needed in order to develop functional treatments. In recent years there have been significant advances regarding in vitro models reproducing important features of AD. However, since a lot of models have been developed, finding the appropriate experimental settings can be puzzling. Therefore, we herein review several types of in vitro skin models mimicking features of AD. Most simple models are two-dimensional culture systems composed of immune cells or keratinocytes, whereas three-dimensional skin or epidermal equivalents reconstitute more complex stratified tissues exhibiting functional barrier properties. In latter models, several hallmarks of AD can be obtained, either by challenging tissues with cocktails of interleukins overexpressed in AD epidermis, or by silencing expression of pivotal genes encoding epidermal barrier proteins. Tissue equivalents co-cultured with lymphocytes or containing AD patient cells are also discussed. Furthermore, each model is placed in the context of a specific study with a brief summary of main results obtained so far. In conclusion, AD in vitro models may become increasingly useful tools to better understand AD pathogenesis, but also to potentially screen new curative or preventive treatments for this disease.